2020
DOI: 10.22435/jki.v10i1.1839
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Kelengkapan Pengisian Formulir Rekonsiliasi Obat terhadap Penggunaan Obat Rasional pada Pasien Rawat Inap di RSU X Bekasi

Abstract: Drug reconciliation is needed to get rational treatment therapy. The purpose of this study was to analyze the relationship between the completeness of filling out the form of drug reconciliation and rational drug use at Bekasi X Hospital. The study design used a cross-sectional comparative study to compare between 56 completed drug reconciliation forms and 133 incomplete drug reconciliation forms. Sampling is done in total sampling. The research sample that fulfilled the inclusion criteria was 189 forms (40.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The medication sheet/drug reconciliation is the part of the medical record that is most often incomplete. Similar to the research at X Hospital Bekasi, the incompleteness of drug reconciliation forms was as much as 70.4% (10). Likewise, research at Husada Hospital Jakarta showed 89% incompleteness in the drug reconciliation section (11).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The medication sheet/drug reconciliation is the part of the medical record that is most often incomplete. Similar to the research at X Hospital Bekasi, the incompleteness of drug reconciliation forms was as much as 70.4% (10). Likewise, research at Husada Hospital Jakarta showed 89% incompleteness in the drug reconciliation section (11).…”
Section: Discussionmentioning
confidence: 58%
“…Meanwhile, based on the Regulation of the Minister of Health Number 269 of 2008 article 2 concerning medical records, medical records must be made in handwriting or electronically, complete, and clear. Referring to the article, the completeness rate of medical records should reach 100% (5,(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation